Penerapan Algoritma Kriptografi Word Auto Key Encryption Dalam Untuk Pengamanan Soal Ujian Berbasis Komputer - Salma Dola Silalahi; Guidio Leonarde Ginting (Journal of Computer System and Informatics (JoSYC), 2020)
The computer-based Final Semester Examination (UAS) held at the Dwiwarna Private Vocational School in Medan was carried out with the help of a web-based application. The application display is divided into two parts, namely the web client accessed by students and the web admin accessed by administrators who have authority. Exam questions are an important aspect of assessing student ability. The problem that occurs is that the record of exam questions stored in the exam database by the admin is very vulnerable to access and can be read by students in the admin menu when inputting questions. This happens because there is no safety record database of questions in the exam web application. Therefore we need a cryptographic security technique. Cryptographic techniques can secure the record of questions by randomizing the value of the incoming question character into a value that is not understood. This research will encrypt the computerized exam database question records with the Word Auto Key Encryption (WAKE) algorithm when the admin enters the questions in the admin web. While the decryption process using the WAKE algorithm is carried out by the application system when the web client is accessed by students by logging in and pressing the start test button